Characterization of soluble microbial products (SMPs) in a membrane bioreactor (MBR) treating synthetic wastewater containing pharmaceutical compounds. (1st October 2016) - Zhang, Dongqing; Trzcinski, Antoine Prandota; Kunacheva, Chinagarn; Stuckey, David C.; Liu, Yu; Tan, Soon Keat; Ng, Wun Jern
Abstract: This study investigated the behaviour and characteristics of soluble microbial products (SMP) in two anoxic-aerobic membrane bioreactors (MBRs): MBRcontrol and MBRpharma, for treating municipal wastewater. Both protein and polysaccharides measured exhibited higher concentrations in the MBRpharma than the MBRcontrol . Molecular weight (MW) distribution analysis revealed that the presence of pharmaceuticals enhanced the accumulation of SMPs with macro- (13, 091 kDa and 1587 kDa) and intermediate-MW (189 kDa) compounds in the anoxic MBRpharma, while a substantial decrease was observed in both MBR effluents. Excitation emission matrix (EEM) fluorescence contours indicated that the exposure to pharmaceuticals seemed to stimulate the production of aromatic proteins containing tyrosine (10.1–32.6%) and tryptophan (14.7–43.1%), compared to MBRcontrol (9.9–29.1% for tyrosine; 11.8–42.5% for tryptophan). Gas chromatography–mass spectrometry (GC-MS) analysis revealed aromatics, long-chain alkanes and esters were the predominant SMPs in the MBRs. More peaks were present in the aerobic MBRpharma (196) than anoxic MBRpharma (133). The SMPs identified exhibited both biodegradability and recalcitrance in the MBR treatment processes. Only 8 compounds in the MBRpharma were the same as in the MBRcontrol . Alkanes were the most dominant SMPs (51%) in the MBRcontrol, while aromatics were dominant (40%) in the MBRpharma . A significant decrease in aromatics (from 16 to 7) in the MBRpharma permeate was observed, compared to the aerobic MBRpharma . Approximately 21% of compounds in the aerobic MBRcontrol were rejected by membrane filtration, while this increased to 28% in the MBRpharma . Highlights: Pharmaceuticals enhanced the production of SMPs with high-MW compounds. Pharmaceuticals stimulated the production of aromatic proteins. Aromatics, long-chain alkanes and esters were the predominant SMPs in MBRs. SMPs exhibited both biodegradability and recalcitrance in the MBRs. Pharmaceuticals influenced the types, structures and properties of SMPs.